Disability Terms in Indonesian Translation of the Qur'an - Mahalli (The Center for Disability Studies and Services Brawijaya University, 2019)
This paper explores how terms of disability represented by Indonesian translation of the Qur'an. By selecting several words listed through the Mu'jamul Mufahras and other corpora, I explore the verses of the Qur'an, and then compare them with the Indonesia translation which has become the most authoritative source in Indonesia, produced by the Ministry of Religion of the Republic of Indonesia. I suggest, through the Social Model of Disability, some terms used in the translation should be contextually reviewed with appropriate terms.